2021
DOI: 10.1016/j.sjbs.2021.05.056
|View full text |Cite
|
Sign up to set email alerts
|

Phytobeneficial and salt stress mitigating efficacy of IAA producing salt tolerant strains in Gossypium hirsutum

Abstract: Salinity is one of the major agricultural concern that significantly limits the crop productivity. The plant growth promoting rhizobacteria (PGPR) may contribute in sustainable crop production under salt stress. The current study was designed to isolate the Indole Acetic Acid (IAA) producing salt tolerant PGPR to promote the growth of cotton ( Gossypium hirsutum , FH-142) and induce its salt stress tolerance. Ten Salt Tolerant (ST) bacterial strains were screened for their PGP trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Rhizospheric isolate Bacillus thuringiensis produced 0.20 µg/ml IAA with 0.1% (w/v) tryptophan after 21 h (Batista et al, 2021). Bacillus siamensis isolated from rhizospheric soil produced 5.14 µg/ml IAA with 0.1% (w/v) tryptophan after 72 h (Saleem et al, 2021). The Bacillus sp.…”
Section: Indole Acetic Acid Productionmentioning
confidence: 99%
“…Rhizospheric isolate Bacillus thuringiensis produced 0.20 µg/ml IAA with 0.1% (w/v) tryptophan after 21 h (Batista et al, 2021). Bacillus siamensis isolated from rhizospheric soil produced 5.14 µg/ml IAA with 0.1% (w/v) tryptophan after 72 h (Saleem et al, 2021). The Bacillus sp.…”
Section: Indole Acetic Acid Productionmentioning
confidence: 99%
“…Moreover, although both strains showed high salinity tolerance, we confirmed that K. marisflavi CSE9 had higher potential ( Szymańska et al, 2020 ). Both strains had IAA synthesis ability, and multifunctional phytohormones play crucial roles in plant growth and development promotion as well as stress resistance ( Numan et al, 2018 ; Khan et al, 2019b ; Saleem et al, 2021 ). Egamberdieva (2009) observed higher crop productivity after the inoculation of wheat with IAA-producing strains under salinity stress than without salt (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthetic pigments of Gossypium hirsutum were significantly reduced under salinity conditions, however, utilization of salt tolerant bacteria including Bacillus subtilus and Bacillus sp. while producing IAA restored cotton systemic resistance to salt-stress [ 27 ]. Analogously, the protective effects of salt tolerant PGPR on photosynthetic pigment were also recorded in Phaseolus vulgaris L. and Arachis hypogaea L. [ 28 ].…”
Section: Discussionmentioning
confidence: 99%